The refinitivization of the infinitive in Finnish - Bielecki, Robert (Lingua Posnaniensis, 2017)
An attempt is made to arrange chronologically the particular stages of the diachronic process of the refinitivization of the infinitive based on their synchronic reflections observable in the contemporary Finnish language. The paper begins with an overview of the morphological and syntagmatic properties of various Finnish infinitive types, and a presentation of the adopted taxonomic approach as opposed to the transformational one. The main part contains a discussion on the details and the substantiation of the particular proposed chronological arrangement of the stages of the process of refinitivization of the infinitive in Finnish. A total of six stages of this process are distinguished, as a consequence of which the connection between the infinitive and finite verb tightens to such an extent that the finite verb metamorphoses into an auxiliary verb, whereas the infinitive metamorphoses into the only carrier of lexical meaning in a new compound verb form.